2018
DOI: 10.1073/pnas.1719905115
|View full text |Cite
|
Sign up to set email alerts
|

Potent and selective antitumor activity of a T cell-engaging bispecific antibody targeting a membrane-proximal epitope of ROR1

Abstract: T cell-engaging bispecific antibodies (biAbs) present a promising strategy for cancer immunotherapy, and numerous bispecific formats have been developed for retargeting cytolytic T cells toward tumor cells. To explore the therapeutic utility of T cell-engaging biAbs targeting the receptor tyrosine kinase ROR1, which is expressed by tumor cells of various hematologic and solid malignancies, we used a bispecific ROR1 × CD3 scFv-Fc format based on a heterodimeric and aglycosylated Fc domain designed for extended … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 60 publications
0
42
0
Order By: Relevance
“…It was demonstrated that targeting a membrane proximal epitope also causes exclusion of the negative regulatory protein CD45 in the synapse, increasing the potency of the T-cell response and killing [15]. This observation that membrane proximal epitopes on the target antigen should provide the greatest TRBA potency has been supported with TRBA-based studies on the cancer targets P-cadherin [225] and ROR1 [226]. Second, the size of the antigen, which can effectively increase the distance within the synapse between the T-cell and target cell, also can affect potency, with much larger targets resulting in lower TRBA potencies [15,221].…”
Section: T-cell Redirecting Bispecific Antibodies (Trbas)mentioning
confidence: 98%
“…It was demonstrated that targeting a membrane proximal epitope also causes exclusion of the negative regulatory protein CD45 in the synapse, increasing the potency of the T-cell response and killing [15]. This observation that membrane proximal epitopes on the target antigen should provide the greatest TRBA potency has been supported with TRBA-based studies on the cancer targets P-cadherin [225] and ROR1 [226]. Second, the size of the antigen, which can effectively increase the distance within the synapse between the T-cell and target cell, also can affect potency, with much larger targets resulting in lower TRBA potencies [15,221].…”
Section: T-cell Redirecting Bispecific Antibodies (Trbas)mentioning
confidence: 98%
“…A potent immunotherapeutic approach was used to develop bispecific antibodies (biAbs) that combine a T cell-engaging arm with a tumor cell-binding arm, for which ROR1 seemed a perfect candidate due to its relatively restricted expression on tumor cells. A ROR1-targeting scFv with a membrane-proximal epitope, R11, which binds to the Kringle domain of ROR1, showed promising in vivo and ex vivo cytotoxicity against ROR1-positive cancer cells [76].…”
Section: Progress In Ror1-targeted Therapiesmentioning
confidence: 99%
“…A significant amount of research and preclinical development is being conducted on developing monoclonal antibodies to target surface ROR1 in CLL and other malignancies 11,42,43 . Also, a considerable body of work has helped us to understand signaling on the extracellular side of ROR1 via Wnt5a in CLL cells 39,44 .…”
Section: Discussionmentioning
confidence: 99%